2004
DOI: 10.1038/sj.gt.3302393
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine genetic adjuvant facilitates prophylactic intravascular DNA vaccine against acute and latent herpes simplex virus infection in mice

Abstract: Intravascular plasmid DNA (pDNA) vaccine encoding herpes simplex virus type 1 (HSV-1) glycoprotein B (gB) effectively induces prophylactic immunity against lethal HSV-1 infection in mice. We investigated whether the vaccine potency is further improved by coadministration of cytokine genes together with a low dose of genetic vaccine. pDNA encoding IL-12, IL-15, IL-18 or IL-21 was capable of elevating survival rates of HSV-1-infected mice when coinjected with 1 mg of gB pDNA, while IL-10 gene delivery failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 43 publications
(58 reference statements)
0
13
0
2
Order By: Relevance
“…They were purified using Qiagen Maxi Prep EndoFree kits (Qiagen). The in vivo gene transfer was performed as described (17). Briefly, BALB/c mice were i.v.…”
Section: Plasmid Vectors and Gene Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…They were purified using Qiagen Maxi Prep EndoFree kits (Qiagen). The in vivo gene transfer was performed as described (17). Briefly, BALB/c mice were i.v.…”
Section: Plasmid Vectors and Gene Transfermentioning
confidence: 99%
“…IL-21 exerts pleiotropic activities on a variety of target cells, alone or in combination with other cytokines (10,11). Several studies have indicated that IL-21 regulates the differentiation, growth, and activation of Th1 (9,(11)(12)(13), Th2 (14), and CTL (15)(16)(17) as well as NK cells (11), whereas myeloid cells, including dendritic cells (18,19) and macrophages (14,20), are also stimulated by this cytokine (21).…”
mentioning
confidence: 99%
“…In view of these findings, it has been suggested that IL-21 can influence both innate and adaptive immunity (43,45). In fact, IL-21 has recently been shown to increase survival rates of HSV-1-infected mice when coinjected with a plasmid DNA encoding HSV-1 glycoprotein B Ag (47), and mice treated with IL-21 have been able to reject tumor cells and develop tumor-specific immune responses (40, 48 -50).…”
mentioning
confidence: 99%
“…In simian immunodeficiency virus (SIV)-infected macaques, furthermore, codelivery of SIV DNA vaccines plus IL-12 or IL-15 cDNA improved Ag-specific CD8+ effector memory T cell responses (Halwani et al, 2008). Another Th1 type cytokine, IL-21 was also demonstrated to be effective as equally as IL-12, IL-15, and IL-18 for augmenting HSV-1 gB-based DNA vaccine potency (Cui et al, 2005). More recently, EP delivery of IL-12 cDNA showed a similar result.…”
Section: Cytokines and Chemokines As Adjuvantsmentioning
confidence: 99%